(untitled) (Research, Society and Development, 2024)
Obesity, a condition that has tripled globally since the 1970s, currently affects about 40% of the adult population, with 13% classified as obese. This increase is associated with a higher risk of cardiovascular complications, the leading cause of death among obese individuals, and also generates high healthcare costs. In the treatment context, semaglutide, a GLP-1 analogue, emerges as a promising innovation for weight loss.Initially approved for the treatment of type 2 diabetes, semaglutide has also shown efficacy in reducing body weight. The drug works by regulating hyperglycemia and decreasing appetite, especially when combined with diet and physical exercise. Studies such as STEP 1 and STEP 2 demonstrate significant weight loss in populations with obesity and diabetes. However, gastrointestinal side effects, such as nausea and vomiting, are common concerns, as well as the high cost of treatment.Semaglutide offers an effective alternative to medications like orlistat and liraglutide, with the advantage of weekly administration. However, long-term safety and financial accessibility remain significant challenges that require continuous attention in research and clinical practice. This article aims to evaluate, through a literature review, the pharmacological repositioning of semaglutide as a weight-loss agent, discussing its mechanisms of action, clinical efficacy, safety, and potential impact on obesity management in different populations. The article was conducted based on a narrative literature review.